Future runoff forecast in Hanjiang River Basin based on Wetspa model and CMIP6 model - Zhou, Xi; Chen, Wei; Liu, Qingtao; Shen, Hongxia; Cai, Siyu; Lei, Xiaohui (Frontiers in Environmental Science, 2022)
In order to comprehensively consider the impact of human activities on runoff simulation and improve the accuracy of runoff simulation, so as to make a more accurate prediction of the future runoff of the Hanjiang River Basin, this study improved the reservoir module of the WetSpa model, adding two parts: reservoir inflow data correction and water storage and outflow data calculation without measured data. Use the improved model to verify its applicability to the Hanjiang River Basin, then, choose the ones who has the most familiar trend with the historical data in the future climate model data (CMIP6). Put the selected data in the model to predict the runoff of Hanjiang River from 2021 to 2060. By analyzing the future runoff trend of Ankang, Huangjiagang and Huangzhuang in the Hanjiang River Basin from 2021 to 2060 and the changes of average runoff, seasonal runoff and monthly runoff compared with the historical period (1981-2020), the conclusions drawn are as follows: (1) The improved WetSpa model has good applicability in the Hanjiang River Basin; (2) The future runoff of Ankang section is decreasing, while that of Huangjiagang and Huangzhuang sections is increasing; (3) Compared with the reference period, the average runoff of the three sections in the future shows an increasing trend, which indicates that there will be flood risk in the future; (4) Compared with the reference period, the runoff proportion of the three sections will increase in spring and winter, and decrease in autumn. Attention should be paid to the risk of drought in autumn. In terms of months, the proportion of runoff from April to June increases, decreases from September to November, and increases and decreases in other months are uncertain.